Development Strategy for Millennials Agri-Socio-Preneur in Ciletuh Palabuhanratu Geopark - Jasuni, Ana Yuliana; Iskandar, Yusuf (Manunggal Halim Jaya, 2026)
Social entrepreneurship in agriculture develops in line with the development of social entrepreneurship. The lack of interest among the younger generation in working in agriculture remains a significant challenge to the development of social entrepreneurship in the agricultural sector, particularly in West Java Province. This study aims to develop a strategy for cultivating agricultural social entrepreneurs among millennial generation farmers, based on the primary challenges in developing agricultural social entrepreneurs and the readiness of millennial farmers in West Java, as well as other stakeholders, to apply the concept of social entrepreneurship to agricultural businesses. The research uses qualitative studies to comprehensively capture the problem situation in developing the human resource capacity of millennial generation farmers, especially in rural West Java. The results of the research indicate that two progressive strategies (SO) need to be implemented. Firstly, the millennial farmer community must ensure that assistance programs from both the government and other parties run smoothly and involve as many parties as possible that may be positively affected. The second strategy is that millennial entrepreneurs, through the use of technology, must innovate to enhance the branding and marketing of processed agricultural products, leveraging existing government programs for support.